PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ANDROID PADA MATA PELAJARAN KERJA BENGKEL DAN GAMBAR TEKNIK - Ika Parma Dewi; Yuni Yuni Meinastria; Nizwardi Jalinus; Rijal Abdullah (Universitas Negeri Padang, 2021)
This study aims to design android-based learning media using the Mit App Inventor Web application in workshop work subjects and engineering drawings for class X industrial electronics engineering at SMA Negeri 1 West Sumatra. This type of research is using the Richey and Klein method which is the development of Desigh and Development (D&D). Richey and Klein stated a focus on design, production, and evaluation. The types of data in this study are quantitative data and qualitative data. The research instrument in the form of a questionnaire used to obtain data regarding the level of feasibility and practicality of learning media. This questionnaire was filled with two material experts, two media experts, and students' responses on a limited test basis. The results of this study are an assessment & user of the feasibility of learning media according to the two material experts using homogeneous 95.45% media experts using homogeneous 86.15% category